Application of N-heterocyclic carbene–Cu(I) complexes as catalysts in organic synthesis: a review - Beig, Nosheen; Goyal, Varsha; Bansal, Raj Kumar (Beilstein Journal of Organic Chemistry, 2023)
N-Heterocyclic carbenes (NHCs) are a special type of carbenes in which the carbene carbon atom is part of the nitrogen heterocyclic ring. Due to the simplicity of their synthesis and the modularity of their stereoelectronic properties, NHCs have unquestionably emerged as one of the most fascinating and well-known species in chemical science. The remarkable stability of NHCs can be attributed to both kinetic as well as thermodynamic effects caused by its structural features. NHCs constitute a well-established class of new ligands in organometallic chemistry. Although initially NHCs were regarded as pure σ-donor ligands, later experimental and theoretical studies established the presence of a significant back donation from the d-orbital of the metal to the π* orbital of the NHC. Over the last two decades, NHC–metal complexes have been extensively used as efficient catalysts in different types of organic reactions. Of these, NHC–Cu(I) complexes found prominence for various reasons, such as ease of preparation, possibility of structural diversity, low cost, and versatile applications. This article overviews applications of NHC–Cu(I) complexes as catalysts in organic synthesis over the last 12 years, which include hydrosilylation reactions, conjugate addition, [3 + 2] cycloaddition, A3 reaction, boration and hydroboration, N–H and C(sp2)–H carboxylation, C(sp2)–H alkenylation and allylation, C(sp2)–H arylation, C(sp2)–H amidation, and C(sp2)–H thiolation. Preceding the section of applications, a brief description of the structure of NHCs, nature of NHC–metal bond, and methods of preparation of NHC–Cu complexes is provided.
Keywords: conjugate addition; [3 + 2] cycloaddition reaction; hydrosilylation reaction; N-heterocyclic carbenes; NHC–Cu complexes; NHC–Cu complexes as catalyst